Transformasi Kurikulum Berbasis Kompetensi dalam Pembelajaran Pendidikan Agama Islam: Menyiapkan Generasi Berkarakter di Era Digital - Juli Yansyah, Muhammad Eko; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Jurnal Pendidikan Dasar, 2024)
The transformation of the Islamic Religious Education (PAI) curriculum into a strategic approach to prepare a strong and relevant generation in the digital era. This study analyzes changes in the design and implementation of a competency-based PAI curriculum to meet the demands of 21st-century competencies, such as critical thinking skills, creativity, digital literacy, and strong religious values. This research investigates how competency components can be aligned with holistic PAI principles to shape students with spiritual, moral, and social awareness. This is done using a descriptive qualitative approach. Research results show that a competency-based curriculum can provide a flexible framework to integrate technology, innovative learning approaches, and a structured Islamic values approach to prepare a generation that is not only knowledgeable in science but also moral and character-driven. With this change, the role of teachers as creative facilitators and continuous evaluators is very important to ensure that the competencies taught align with the needs and challenges of the times. According to this research, PAI teachers must be continuously trained to master the use of technology in teaching and the comprehensive development of their students' competencies.